Metaplastic carcinoma breast (IDC and chondrosarcoma): a rare entity - Kalra, Deepesh; Kaushik, Bhanu; Gupta, Shalu; Tanwar, Pradeep; Khan, Sami Anwar (International Surgery Journal, 2018)
Metaplastic breast carcinoma is very rare neoplasm. Authors report a case of metaplastic breast carcinoma containing characteristic features of infiltrating ductal carcinoma and chondrosarcoma. A 62-year-old female presented with complaint of a lump in the right breast for the last 2 years. FNAC was suggestive of mucinous tumour. Tru-cut biopsy had been performed outside the institution, which was suggestive of a Ductal carcinoma with mucinous component. Modified radical mastectomy of the right breast was performed and histopathology was suggestive of infiltrating ductal carcinoma and chondrosarcoma of the right breast. All resected lymph nodes were free of metastasis. Immunohistochemistry was suggestive of a metaplastic carcinoma with components of ductal carcinoma and chondrosarcoma with moderately positive ER, negative PR, positive Pancytokeratin in ductal carcinoma component, positive S-100 and KI-67.